The chosen : a novel - Potok, Chaim (New York, Simon and Schuster, 1967)
A novel about a Jewish family living in the Williamsburg section of Brooklyn in the 1940's.
A baseball game between two Jewish parochial schools is the setting for a meeting between the son of a Hasidic rabbi and the son of an Orthodox.
970
Keywords: Jewish families -- Fiction; Fathers and sons -- New York (State) -- New York -- Fiction; Jews -- New York (State) -- Fiction; Jews -- Fiction; Friendship -- Fiction; Hasidim -- Fiction; Jewish teenagers -- United States -- Fiction; Jewish youth -- United States -- Fiction; Jews -- United States -- Fiction; Brooklyn (New York, N.Y.) -- Fiction; Religious fiction; Domestic fiction